Efficient Sowing Unit - Sadulla Aminov; Makhammatdin Kaypov; Bakhtiyar Artikbaev (International Scientific and Current Research Conferences, 2021)
The article discusses the results of research on a method of weed control that allows farms to save costs on weeding weeds, removing soil crust, improving the structure of the soil and giving additional products by increasing yields. The results of the experimental study have shown sufficient efficiency of the sowing unit.